The Main Factors and Trends of Urbanization in Kazakhstan: Analysis and Recommendations - N. K. Nurlanova; A. Tleuberdinova; N. Saparbek (Экономика: стратегия и практика)
With the development of industry, the industrialization of agriculture, the strengthening of Industry 4.0 trends in all countries of the world, the trends of migration of rural residents to cities, and the pace of urbanization are increasing. The purpose of the article was to study the main factors determining the trends, intensity, and specificity of urbanization processes in Kazakhstan. The methods of retrospective analysis, analogies, logical analysis, generalizations, demographic and economic statistics, index, graphic, comparative analysis, absolute and relative indicators of demography and migration, methods of the theory of differentiated urbanization are used. Specific methods were applied to calculate the coefficients of urbanization intensity. To achieve the goal, a comparative analysis of theoretical views on trends and factors of urbanization was carried out. Based on statistical data, a comparative analysis of the birth rate, the level, and quality of life, the level of poverty in cities and villages of Kazakhstan was carried out. The dynamics, orientation, and territorial distribution of urbanization processes are revealed. To determine the hierarchies of cities depending on the population, Zipf curves were calculated, ranking of cities was carried out. It is concluded that the processes of urbanization in the country are uneven, as well as that the factors of urbanization are fully manifested in Kazakhstan’s conditions and determine its trends and intensity. Based on the identified trends and problems of urbanization, recommendations on the choice of the main directions and mechanisms for regulating the processes of urbanization in Kazakhstan are substantiated.